BEYOND THE MONEY: A CASE STUDY ON THE BENEFIT OF HAND-DRAWING BATIK TO FEMALE BATIK WORKERS IN JARUM KLATEN REGENCY - Widhi Handayani; Augustinus Ignatius Kristijanto; Arianti Ina Restiani Hunga (Jurnal Kawistara, 2018)
Batik is a cultural product of Indonesia and it is produced by home industries under Putting Out System (POS). Although batik home industries are beneficial economically, their impacts on environment tend to be destroyed due to water pollution resulted from the process of POS. Moreover, batik production by POS is considered to disadvantage female homeworkers. This paper aims to explain the benefit of batik industries in Jarum Village, Klaten toward female homeworkers, even if water pollution occurs in the village. Batik industries give benefit because they provide employment for female homeworkers in Jarum Village. Unfortunately, the benefit from batik production not yet received by some female homeworkers due to low wages they get, in addition to the pollution which could contaminate the groundwater they use for domestic activities. Finally, batik benefits are not merely regarding economics context as batik provides a space for self-actualization, mainly to the elder workers.